Серлөрем бар: лирика, юмор / Шәукәт Галиев - Галиев Шаукат (Татарстан китап нәшрияты, 2002)
Экземпляры: КХ (20030212) / Инвентарный номер: 1047384 / Цена: 15.00 / Сис.шифр: С(Тат) / Авт.знак: Г 15 / ГРНТИ: 17 / ББК: 84(2)